Research and publications in Islamic perspective (part 2: experimental results) - Khedher, Akram M Z M (KICT, IIUM, 2022)
This article is part 2 of “Research and Publications in Islamic Perspective” and is focuses on the experimental results, while part 1 was an introductory on this topic.